1998
DOI: 10.1080/03033910.1998.10558191
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the effectiveness of a chronic pain management programme

Abstract: The UCD community has made this article openly available. Please share how this access benefits you. Your story matters! (@ucd_oa) Some rights reserved. For more information, please see the item record link above.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2005
2005
2010
2010

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 16 publications
0
4
0
Order By: Relevance
“…Although the benefits are not clearly found in results from standardized measures of functional disability (RMDQ-A) and mood (HADS), they are suggested by progress through the pain stages of change (PSOCQ), good and active attendance despite significant physical handicaps, feedback from the weekly questionnaires, staff observation of groups' progress and the development of local self-help support groups advocating for pain patients. It was disappointing that, since treatment effect sizes are greatest for mood in pain management programmes (Collins et al, 1998) no similar improvement was found: although anxiety scores did reduce, they only approached significance ( p < 0.09) (Table I). However, this may reflect the more rigorous selection of patients described earlier for specialist programmes (Turk & Rudy, 1990 that is not representative of the chronic pain population found in this sample.…”
Section: Discussionmentioning
confidence: 77%
See 3 more Smart Citations
“…Although the benefits are not clearly found in results from standardized measures of functional disability (RMDQ-A) and mood (HADS), they are suggested by progress through the pain stages of change (PSOCQ), good and active attendance despite significant physical handicaps, feedback from the weekly questionnaires, staff observation of groups' progress and the development of local self-help support groups advocating for pain patients. It was disappointing that, since treatment effect sizes are greatest for mood in pain management programmes (Collins et al, 1998) no similar improvement was found: although anxiety scores did reduce, they only approached significance ( p < 0.09) (Table I). However, this may reflect the more rigorous selection of patients described earlier for specialist programmes (Turk & Rudy, 1990 that is not representative of the chronic pain population found in this sample.…”
Section: Discussionmentioning
confidence: 77%
“…When comparing the results obtained here with traditional pain management programmes, which typically obtain 50-60 per cent 'improvement' (Flor et al, 1992) particularly in mood and activity level (Collins et al, 1998), the results of this study are not so powerful. What has to be born in mind is that this patient group experienced a complex of problems, with long-term illness and disability, mental health problems, motivational difficulties, medical dependency, poor financial and employment opportunities and social isolation.…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations